EFFECT OF TECHNOLOGY, EMPLOYEE COMPETENCY AND LEADERSHIP ON OPERATIONAL PERFORMANCE AT MALEO PRODUCER PLATFORM-MADURA OFFSHORE PT. RADIANT UTAMA INTERINSCO - Gunawan, Rian; Sugeng Suroso; Faroman Syarief (Dinasti International Journal of Management Science, 2022)
Knowledge of technology, employee competence, and leadership is important for the company, so that its use needs to be managed properly in the context of improving the company's operational performance. The research aims to determine the effect of technology, employee competence and leadership on operational performance at Madura Offshore gas production facility PT. Radiant Utama Interinsco, Tbk. The research is quantitative research method with analysis techniques for hypothesis testing using Smart PLS version 3.3.7. Population used 100 person who all of responden are employees at Madura Offshore gas production facility PT. Radiant Utama Interinsco, Tbk. The research results show that technology, employee competence and leadership have effect on operational performance. It reflects that the better technology, employee competence and leadership will make better operational performance to achieve company goals.